2012
DOI: 10.1111/j.1445-2197.2012.06122.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative fluid therapy in elective colectomy in an enhanced recovery programme

Abstract: Intraoperative fluid restriction can be employed uniformly in ASA 1-3 patients undergoing colectomy. Post-operative administration of greater fluid volumes was associated with adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…9,10,12,16,17,37,38 This also holds true for high-risk patients. 39 Transient hypotension is an acknowledged side effect of neuraxial blockade; postoperatively, about 10%e20% of patients are affected. 27,30,32,33,40 In the current series, hypotension occurred in patients with or without intrathecal injections (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,12,16,17,37,38 This also holds true for high-risk patients. 39 Transient hypotension is an acknowledged side effect of neuraxial blockade; postoperatively, about 10%e20% of patients are affected. 27,30,32,33,40 In the current series, hypotension occurred in patients with or without intrathecal injections (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The current study confirmed that the ERAS group had a significantly lower occurrence of complications, and identified DVT as a major complication prevented by ERAS strategy. Limited fluid therapy and early oral diet have been reported to not only promote the resumption of bowel function and lessen the stress reaction of patients, but also decrease postoperative complications and shorten hospitalization time (12). Meanwhile, good pain control has also been recommended to achieve rapid recovery and discharge and decrease the occurrence of post-operative complications (2).…”
Section: Discussionmentioning
confidence: 99%
“…Early postoperative oral nutrition has been reported to reduce catabolism, lessen stress reaction, and decrease resting energy expenditure and postoperative complications such as nausea, vomiting, bloating or enteroparalysis (Srinivasa et al 2012; Nygren et al 2005). Most patients can eat normal food at day one after liver surgery, and we recommend early oral intake to accelerate resumption of bowel function.…”
Section: Discussionmentioning
confidence: 99%